1985
DOI: 10.1126/science.2994217
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of AIDS: Current Status and Future Prospects

Abstract: The reported incidence of acquired immune deficiency syndrome (AIDS) continues to increase in countries throughout the world. On the basis of a polynomial model for extrapolation, the cumulative number of cases diagnosed and reported since 1981 in the United States is expected to double during the next year with over 12,000 additional cases projected to be diagnosed by July 1986. The annual incidence rates for single (never-married) men in Manhattan and San Francisco, intravenous drug users in New York City an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
0
5

Year Published

1986
1986
1998
1998

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 507 publications
(121 citation statements)
references
References 40 publications
(16 reference statements)
4
112
0
5
Order By: Relevance
“…It has been shown frequently that smoking is associated with natural menopause (1)(2)(3)(4)(5)(6). Other studies have found smoking to be associated with the inability to become pregnant (6), lowered estrogen levels in the luteal phase (7), and alterations in the levels of gonadotropins and other hormones that may affect ovarian function (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown frequently that smoking is associated with natural menopause (1)(2)(3)(4)(5)(6). Other studies have found smoking to be associated with the inability to become pregnant (6), lowered estrogen levels in the luteal phase (7), and alterations in the levels of gonadotropins and other hormones that may affect ovarian function (8).…”
Section: Discussionmentioning
confidence: 99%
“…As THE NUMBER OF PERSONS WITH acquired immunodeficiency syndrome (AIDS) increases, most of the nation's health care workers will need to learn how to care for people with AIDS and how to avoid exposure to the AIDS virus, which is named the human immunodeficiency virus (HIV) (1,2). The evidence suggests that many providers are uneasy about the idea of caring for someone with AIDS (3,4).…”
mentioning
confidence: 99%
“…Here we summarize work on AIDS retrovirus, and do not treat epidemiology or public health aspects, beyond noting the following. First, in 1985 the cumulative total of reported AIDS cases passed 104 in the U.S.A. and 103 in western Europe; the disease is thus now of major public health concern (Curran et al, 1985). Second, systems to test for the presence of serum antibodies to AIDS retrovirus have now come into widespread use, most significantly in screening of blood donated for transfusion.…”
Section: The Virology Of Acquired Immune Deficiency Syndromementioning
confidence: 99%
“…In fact, one senior regulator of the time confided to the author (years afterwards) that when he first heard the author describe the results of characterization of the CHO cells expressing tPA (basically, CHO cells are tumorigenic in nude mice and express retrovirus-like particles), he feared that the desire to investigate these products in humans would rekindle the spirited debates of 1954-1975 on the use of CCLs to prepare biologicals for human use. The then-recent discovery of human immunodeficiency virus (HIV) and its transmission to recipients of blood and plasma products and their derivatives (Curran et al, 1985) fueled concern in the regulatory community over the possibility of iatrogenic transmission of pathogenic viruses, especially retroviruses. There was also theoreticallybased concern in a few ex-US regulatory agencies over the possibility of transmissible spongiform encephalopathies (TSEs) as a potential contaminant of medical products based on earlier studies of ovine scrapie and human kuru.…”
Section: Thenmentioning
confidence: 99%